Case Report: Acute lead poisoning from bullet ingestion in a captive cheetah (Acinonyx jubatus) in Namibia: implications for wildlife management - Hauw, Catherine; Schmidt-Küntzel, Anne; Basto, Ana F.; Yabe, John; McCann, Niall; Díez-León, María; Marker, Laurie (Frontiers in Veterinary Science, 2025)
The case study describes a suspected instance of lead poisoning in a cheetah in Namibia. While lead toxicity is well-documented in carnivorous birds, this case study is only the second of two publications on lead poisoning in cheetahs. Furthermore, we included the first video documentation of acute lead poisoning in this species, showcasing neurological signs of heightened excitability, arched back, raised tail, and excessive salivation. The cheetah died within 48h of first report of clinical signs and post-mortem examinations revealed a bullet in the cheetah's stomach and extensive organ necrosis with multifocal hemorrhages in hepatic and renal tissues. The ingestion of the bullet likely resulted from the feeding of a game-meat carcass which was hunted with lead-ammunition. The cheetah's liver and kidney samples contained lead levels of 38.25 and 56.03 mg/kg dry weight, respectively, consistent with acute lead poisoning. Furthermore, bone lead was shown to be of 1.44 mg/kg dry weight suggesting additional non-lethal chronic exposure. This case highlights the challenges of wildlife management associated with lead ammunition use, particularly in the context of carcass feeding, a common practice for captive carnivores in southern Africa.